Odd Thomas - Koontz, Dean R. (Dean Ray), 1945- (Koontz, Dean R. (Dean Ray), 1945- Odd Thomas novel, 2012)
Odd Thomas is a short-order cook in a small desert town and also the reluctant confidant of dead people. The dead can communicate with Odd Thomas, which makes his life a little complicated. But when a stranger surrounded by evil comes to town, everything gets much, much worse.